Loss aversion in social image concerns - Vasilisa Petrishcheva; Gerhard Riener; Hannah Schildberg-Hörisch (Experimental Economics, 2022)
Does loss aversion apply to social image concerns? In a laboratory experiment, we first induce social image in a relevant domain, intelligence, through public ranking. In a second stage, subjects experience a change in rank and are offered scope for lying to improve their final, also publicly reported rank. Subjects who care about social image and experience a decline in rank lie more than those experiencing gains. Moreover, we document a discontinuity in lying behavior when moving from rank losses to gains. Our results are in line with loss aversion in social image concerns.
Keywords: C91; D91; 330; Loss aversion; Social image concerns; Lying behavior; Laboratory experiment